Do glycoalbumin levels preferentially reflect changes in postprandial glucose excursions? - Paul, S; Holman, R (Wiley, 2017)
Aims To evaluate whether plasma glycated albumin, which provides an integrated measure of plasma glucose levels over the preceding 2–4 weeks, better reflects changes in postprandial glucose excursions than HbA1c. Methods People with suboptimum glycaemic control on dual oral therapy were enrolled in the Treating‐to‐Target‐in‐Type 2 diabetes (4‐T) trial, in which participants were randomized to the addition of once‐daily basal insulin, twice‐daily biphasic insulin or thrice‐daily prandial insulin. Glycated albumin levels were assayed enzymatically from baseline and 1‐year fasting plasma samples. We evaluated robust correlations of glycated albumin and HbA1c both with fasting and postprandial glucose levels at these two time points, and with insulin‐induced changes in the postprandial excursion. Results Requisite data were available for 625 of the participants in the 4‐T trial. Their mean (±sd) age was 62 ± 10 years and body weight was 85.8 ± 15.9 kg, and their median (interquartile range) diabetes duration was 9 (6, 13) years. Partial correlations at baseline and 1 year between postprandial glucose excursions and glycated albumin/HbA1c, after adjusting for fasting glucose, were 0.27/0.15 and 0.22/0.18, respectively. Glycated albumin, compared with HbA1c, explained 66% more of the variation in postprandial glucose excursions at baseline. At 1 year, postprandial glucose excursions on basal, biphasic and prandial and insulin therapy were reduced by 0.43, 0.78 and 1.88 mmol/l, respectively. These reductions were associated with changes in both glycated albumin and HbA1c (P < 0.01), with a stronger association for glycated albumin. Conclusion Changes in glycated albumin and HbA1c reflect changes in postprandial glucose excursions to a similar extent.